Modelling of double porosity clays in a mini-centrifuge. Issue 1 (March 2009) - Najser, J.; Pooley, E.; Springman, S.M.
Abstract : Physical modelling of double porosity clay was carried out in a mini-centrifuge. These tests were performed as a preliminary study for modelling a case history from Northern Bohemia in the large geotechnical drum centrifuge. The main aim of these tests was to investigate the effect of lump size distribution on soil compressibility during self-weight consolidation. In addition, oedometer tests were carried out to investigate the response of double porosity soil to one dimensional loading with the attendant degradation in structure. Comparison with large centrifuge test results showed good correlation, despite the simple test procedure.